Binarized revocable biometrics in face recognition - Pang, Ying Han; Ngo, David Chek Ling; Teoh, Andrew Ben Jin (Springer Berlin Heidelberg, 2005)
This paper proposes a novel revocable two-factor authentication approach which combines user-specific tokenized pseudo-random bit sequence with biometrics data via a logic operation. Through the process, a distinct binary code per person, coined as bio-Bit, is formed. There is no deterministic way to acquire bio-Bit without having both factors. This feature offers an extra protection layer against biometrics fabrication since bio-Bit authenticator is replaceable via token replacement. The proposed method also presents functional advantages of obtaining zero equal error rate and yielding a clean separation between the genuine and imposter populations. Thereby, false accept rate can be eradicated without suffering from the increased occurrence of false reject rate.